Pemahaman Dan Pengembangan Alinea Dalam Penulisan Dan Penerjemahan Bahasa Indonesia Dan Bahasa Arab - Muhammad Yasin; Kamaluddin Abuanawas; A. Abdul Hamzah (Departement of Mathematics Education, 2024)
This research explores the importance of proper paragraph writing and translation from Indonesian to Arabic. A qualitative descriptive method is used to analyze paragraph writing and translation techniques. Data were collected from various literatures such as books, journal articles, and trusted websites. Analysis was conducted through literature review and document analysis, with data validation using source triangulation and peer review. The results indicate differences and similarities in the structure, requirements, characteristics, as well as writing and translation techniques of paragraphs in both languages. This research provides a deeper understanding of paragraph writing and translation, serving as a reference for writers and translators in both languages. It is hoped that this research can enhance the quality of written works and translations in Indonesian and Arabic.